(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Mediterranean black scale, Saissetia oleae (Oliver) (Hemiptera: Coccidae) is the most important pest of olive in Egypt. Indigenous parasitoids of S. oleae from different localities were collected, reared and mass produced; about 113,000 parasitoids were released for augmentative biological control. At three locati ons in Egypt, several releases of the following indigenous parasitoids were made: Alaptus sp., Baeoanuisa sp., Coccophagus lycimnia (Walker), Diversinervus elegans Silvestri, Metaphycus bartletti Annecke & Mynhardt, M. flavus (Howard), M. helvolus (Compere), M. zebratus (Mercet), Microterys flavus (Howard), Parechthrodryinus coccidiphagus (Mercet) and Scutellista caerulea (Fonscolombe). The indigenous parasitoid M. bartletti plays an important role in controlling S. oleae in Egypt. Maximum parasitism rates by this species reached 83, 56% and 33% on the Northern Coast, at Mersa Matruh and El-Arish, respectively.